Thyroid hormone responses to acute aerobic exercise - Baydil, Bilgehan; Akgül, Mustafa Ş. (Sergii Iermakov, 2021)
Background and Study Aim. Thyroid hormone responses to acute maximal aerobic exercise is still unclear, so the aim of the study is to investigate the effect of acute maximal aerobic exercise resulting in fatigue on blood thyroid levels in men and women. Material and Methods. The study included 8 male and 7 female subjects who did not actively exercise. Both group participants were students in the Kastamonu University in the period of study. The heights, weights, resting hearth rates and 5 cc. venous blood samples of subjects were taken before the exercise. The subjects warmed up for ten minutes before they had 20 m shuttle run. The purpose of this test was to tire the subjects to the exhaustion. The heart rate were measured at the end of the test in order to determine the exhaustion levels of the participants. The 5 cc. venous blood samples were taken again just after the exhaustion exercise. Statistical analysis was carried out using Statistical Package for the Social Sciences (SPSS) 23 program (SPSS Inc. Chicago. II. USA). P value was set at p<0.05. Results. When results were compared between both sexes, no significant difference was found among variables (p>0.05). There was significant change in TSH values in all group. They increased following the exercise compared to pre-exercise values. Moreover, total T3 decreased in all group. No other significant difference was found in free T3 and free T4 variables. Conclusions. In conclusion, thyroid responses to exercise emerge in a very complex way, which makes it difficult to reach a clear conclusion about its effects. The reason why the results are so contradictory is that the duration and intensity of the exercise, age, not being able to control the diet, and the timing of collection of blood samples after exercise.
Keywords: Thyroid hormones; Heart rate; High-Intensity Interval Training; Significant difference; Endocrinology; Health Sciences; Orthopedics and Sports Medicine; Internal medicine; Aerobic exercise; Thyroid; LC8-6691; thyroid stimulating hormone; Special aspects of education; Hormone; Statistical significance; Venous blood; aerobic exercise; Blood pressure; Medicine; fatigue; Sports Science and Performance Analysis; Training Load; Physical therapy; 3. Good health